2017
DOI: 10.17586/2220-8054-2017-8-6-723-731
|View full text |Cite
|
Sign up to set email alerts
|

Nanocluster structure deduced from AC-STEM images coupled to theoretical modelling

Abstract: Determining the atomic structure of nanoclusters is a challenging task and a critical one for understanding their chemical and physical properties. Recently, the high resolution aberration corrected scanning transmission electron microscope (AC-STEM) technique has provided valuable information about such systems, but the analysis of the experimental images has typically been qualitative rather than quantitative. A method is presented for detailed analsis of AC-STEM images combined with theoretical modelling to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 31 publications
(31 reference statements)
1
1
0
Order By: Relevance
“…The calculated cluster structures presented here can be compared with experimental observations of structural features in Au and Pt clusters. The lowest energy structure of Au 55 found here is in good agreement with previous computational [17][18][19]31 and experimental 16 studies that identify the lowest energy isomers of Au 55 to be a family of distorted, chiral clusters. The exact structure of the global minimum depends highly on the theoretical description of the atomic interactions (see ESI † for detailed discussion).…”
Section: Comparison Of Experiments and Theorysupporting
confidence: 90%
See 1 more Smart Citation
“…The calculated cluster structures presented here can be compared with experimental observations of structural features in Au and Pt clusters. The lowest energy structure of Au 55 found here is in good agreement with previous computational [17][18][19]31 and experimental 16 studies that identify the lowest energy isomers of Au 55 to be a family of distorted, chiral clusters. The exact structure of the global minimum depends highly on the theoretical description of the atomic interactions (see ESI † for detailed discussion).…”
Section: Comparison Of Experiments and Theorysupporting
confidence: 90%
“…27,28 A variety of calculations have been performed for both Au and Pt clusters, from survey calculations over a large cluster size range using an empirical potential 29 to detailed global optimisations at a few selected sizes. 17,18,30,31 Many studies have provided support for the notion of a crossover (either gradual or abrupt) from Ih to Dh to FCC as the cluster size is increased. 20,29,[32][33][34][35][36] However, it should be noted that both Dh and FCC have been shown to be competitive structures over a wide range of sizes; 29,37 recently, it has been found that Dh and FCC motif preference continues to oscillate even at sizes up to 4000 atoms.…”
Section: Introductionmentioning
confidence: 99%